Colpa o rischio? Sulla coesistenza di due princìpi e sulla loro difficile legittimazione morale - Bondolfi, Alberto 1946- (2013)
This article aims to highlight the «eternal» character of the arguments put forward in favor or against the moral legitimacy of penal sanctions. Contemporary dis-cussions tend to replace the criterion of guilt with that of the risk of recidivism and, in doing so, impose a paradigm shift on the entire judicial system. It is argued that, from a moral point of view, this paradigm shift has clear limits. Moreover, the undifferentiated use of the criterion of «dangerousness» in the context of penal sanctions is shown to be highly problematic also when considered from a theological perspective. The article argues for an intermediate position. On the one hand, significance is conceded to the category of dangerousness; on the other hand, it is insisted that this significance must be thought of as constrained by the rules of a law that respects the fundamental rights of every person.